Performance evaluation of TCP, UDP and DCCP traffic over 4G network - Kamil, Wisam Abduladheem; Awang Nor, Shahrudin; Alubady, Raaid (MAXWELL Science Publication, 2015)
Fourth Generation (4G) mobile systems has been used more widely than the older generations 3G and 2G. Among the reasons are that the 4G’s transfer rate is higher and it supports all multimedia functions.Besides, its’ supports for wide geographical locus makes wireless technology gets more advanced.The essential goal of 4G is to enable voice-based communication being implemented endlessly.This study tries to evaluate if the old protocols suit with this new technology.And which one has the best performance and which one has the greatest effect on throughput, delay and packet loss.The aforementioned questions are crucial in the performance evaluation of the most famous protocols (particularly User Datagram Protocol (UDP), Transmission Control Protocol (TCP) and Datagram Congestion Control Protocol (DCCP)) within the 4G environment.Through the Network Simulation-3 (NS3), the performance of transporting video stream including throughput, delay, packet loss and packet delivery ratio are analyzed at the base station through UDP, TCP and DCCP protocols over 4G’s Long Term Evaluation (LTE) technology.The results show that DCCP has better throughput and lesser delay, but at the same time it has more packet loss than UDP and TCP. Based on the results, DCCP is recommended as a transport protocol for real time video.